Pharmacoepidemiology and public health day: learning beyond the classroom - Shapri, Nik Aisyah Najwa Nik Mustaffa; Zakaria, Yuslina (Faculty of Pharmacy, 2026)
Pharmacoepidemiology and Public Health Day was successfully conducted on 19 December 2025 as part of the learning activities for second-year pharmacy students. The event, which involved 232 students, aimed to reinforce core concepts in pharmacoepidemiology and public health by moving beyond traditional classroom teaching and providing opportunities for students to apply theoretical knowledge in an interactive and engaging setting.During the event, students participated in booth-based presentations, where they showcased key epidemiological and public health topics through creative and evidence-based approaches. Each group introduced their assigned topic, demonstrated its application in research using published journal articles, and explained their literature search strategies, including the use of databases and Boolean operators. This format encouraged peer-to-peer learning and active engagement among students and evaluators.